Embedded system application development on Raspberry Pi 4 – Driver Monitoring System (DMS) - Low, Chang Chuan (Nanyang Technological University, 2022)
Modern vehicular safety devices such as the three-point safety seatbelt and airbags are well established technologies aimed to improve the safety of the driver and occupants of vehicles and are already found in majority of existing vehicles on our roads. Yet, these safety systems are applicable only when accidents have already occurred. Advancements in technology and modern electronics have encouraged vehicle manufacturers to adapt new vehicles with active safety systems aimed to prevent accidents from happening.